METODE TEAM QUIZ DAPAT MENINGKATKAN MINAT BELAJAR SISWA SD NEGERI 13 JAYA - Ismail Darimi; Irman Siswanto; Bachtiar Ismail (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
Ideally in the learning process students are expressed interest if students make their learning as an interest, because interest will make students learn seriously. The reality is that students are lacking in enthusiasm or not motivated to learn well, so it needs a method that can increase students' learning interest in the material in question. This study has obtained results that the use of team quiz methods can improve student learning outcomes. This can be seen from the results of the analysis in cycle I and cycle II, showing an increase in student learning completeness from cycle I to cycle II. This result is clearly seen from the average student learning outcomes in the first cycle with a percentage of 74.40% while in the second cycle the percentage is 89.20%. This proves that student learning completeness has increased in cycle II. This proves that learning has a classical improvement. The use of team quiz method can increase students 'interest in learning can be seen based on students' interest in the use of team quiz method in learning PAI reaches 92.4% of the total number of students. This percentage is included in the very high category. So it was concluded that there was an increase in students' learning interest in PAI learning by using the team quiz method. Students are more active and have an interest in learning because the material presented is easy to remember and understand.